FINANCIAL INCLUSION AN ENABLER FOR GROWTH IN DIGITAL INDIA: ANEMPIRICAL APPROACH - Sharma, Gazal; Mathur, Dr. Monika (The journal of contemporary issues in business and government, 2022)
Purpose: An inclusive financial system is essential for absolute growth of a nation. The purpose of the study is firstly to examine the key trends in growth of Mobile banking in India for the last decade (2010-2020). Secondly to determine the key enablers for Financial inclusion in digital India and to analyse the relation between Financial inclusion index and Average rate of growth of real GDP in India Design/Methodology: The study is based on complete secondary data and it has been collected from official government databases such as RBI, NPCI, World Bank, Global Findex Databases, PMJDY, NSFI etc. The research methodology is descriptive research design. The collected data are analysed using statistical tools such as Graphs, Tables, Correlation and Ordinary Least square inEviews 12. Findings: The study provides insight on the trend of Digital financial inclusion policies in India. India has received greater advantages from the Jan Dhan and Mobile Banking policies throughout the past few years. The study concludes thatin order to create a sustainable environment for the end users there is a need to encourage the regulators, the telecom service provider and the financial institutions. Practical Implication: Financial inclusion and mobile Banking in any growing economy synchronizes with each other. This paper studies the coordination between the two although both are expanding in India. There is a need of customer centric approach as far as technological growth is concerned. The findings of the study may further help to nourish the ongoing procedure and policies of the two schemes and may upgrade the standard of Digital India. Originality/Value: Financial inclusion has been more widely acknowledged as a key contributor towards socio-economic development and Digitalization has become significant for Indian Banking sector. The revolutionary combination of the two major initiatives leads to greater social cohesion and shared economic growth. The paper has also focusedon retail payment systems of USSD portal based M-Banking which is led by the National Payment Corporation of India.